Grabbing "Green": Markets, Environmental Governance and the Materialization of Natural Capital. Issue 1 (March 2013) - Corson, Catherine; MacDonald, Kenneth Iain; Neimark, Benjamin
Over the past two decades, the incorporation of market logics into environment and conservation policy has led to a reconceptualization of "nature." Resulting constructs like ecosystem services and biodiversity derivatives, as well as finance mechanisms like Reducing Emissions from Deforestation and Forest Degradation, species banking, and carbon trading, offer new avenues for accumulation and set the context for new enclosures. As these practices have become more apparent, geographers have been at the forefront of interdisciplinary research that has highlighted the effects of "green grabs"—in which "green credentials" are used to justify expropriation of land and resources—in specific locales. While case studies have begun to reveal the social and ecological marginalization associated with green grabs and the implementation of market mechanisms in particular sites, less attention has been paid to the systemic dimensions and "logics" mobilizing these projects. Yet, the emergence of these constructs reflects a larger transformation in international environmental governance—one in which the discourse of global ecology has accommodated an ontology of natural capital, culminating in the production of what is taking shape as "The Green Economy." The Green Economy is not a natural or coincidental development, but is contingent upon, and coordinated by, actors drawn together around familiar and emergent institutions of environmental governance. Indeed, the terrain for green grabbing is increasingly cultivated through relationships among international environmental policy institutions, organizations, activists, academics, and transnational capitalist and managerial classes. This special issue of Human Geography brings together papers that draw on a range of theoretical perspectives to investigate the systemic dimensions and logics mobilizing green grabs and the creation of new market mechanisms. In inverting the title – "grabbing green" instead of the more conventional green grabs – we explore how "the environment" is being used instrumentally by various actors to extend the potential for capital accumulation under the auspices of "being green." Using a diversity of empirical material that spans local to global scales, the papers reveal the formation of the social relations and metrics that markets require to function. They identify the "frictions" that inhibit the production of these social relations, and they link particular cases to the scalar configurations of power that mobilize and give them shape.